Anterior Abdominal Wall Endometriosis Following Caesarean Section: Two Rare Cases - Meryem Belmajdoub; Sofia Jayi; Fatima Zehra Fdili Alaoui; Hekmat Chaara; Moulay Abdelilah Melhouf (European Scientific Journal, ESJ, 2019)
Parietal endometriosis is a rare clinical entity, whose pathophysiology remains unclear. It occurs most often after gynecological or obstetrical surgery. The clinical picture is relatively unspecific. Medical imaging is not very contributive. Only histological examination of the operative specimen can confirm the diagnosis. Surgical treatment must be wide enough to prevent recurrence. We report two cases of abdominal wall endometriosis occurring on caesarean section scar. Through these two cases, we will highlight the characteristics of this pathology including prognosis, which will help the practitioners in understanding the role of diagnosis and early management of this entity and its prevention during gynecological or obstetrical surgery.